Preventing transformer internal resonance under very fast transient overvoltage using RC surge suppressor - Babaei, M.; Abu-Siada, Ahmed (Institute of Electrical and Electronics Engineers, 2017)
© 1994-2012 IEEE. This paper investigates the feasibility of a cost effective method to prevent internal resonance in power transformers connected to gas insulated substation (GIS) due to very fast transient overvoltage (VFTO) within the GIS. Power transformer internal resonance takes place if one of the VFTO frequencies matches with the transformer natural frequency. If the system is not equipped with adequate damping scheme for such transients, transformer catastrophic failure may take place causing harmful impacts on the environment including fire and oil spillage. In this paper, the feasibility of utilizing RC surge suppressor to avoid power transformer internal resonance is investigated through the simulation of a real 400kV gas insulated substation located in the north of Iran and connected to a 250MVA, three phase power transformer. Several RC design topologies are analysed and the most effective topology to suppress high risk frequencies of VFTO is highlighted. In contrary to the existing resonance suppressing approaches that call for modifications in the GIS infrastructure, the proposed method in this paper is a cost effective technique that can be implemented within existing gas insulated substations without any change in its structure.